Organização sindical : o caso Sadia Concórdia - Pissolo, Ivandro José (2006)
This research studies the theme of syndicalism, dealing with the case of workers organization in the Sadia S. A. industry, Concórdia Unit, Santa Catarina. It s the study of a case, so, some ideas of this thematic field were approached from the local profile, a justifiable fact considering the regional character of this work. The aim of this text is to clear up some questions around the region s popular imaginary, as for example: where from comes the people s fear when talking about unionism? Why do people think Sadia is so important in the region? We show criticism, analysis and discussions on the labor-union organization of this industry, trying to bring light to themes not yet discussed in the region. This work also deals with the interference of the industry, other unions and from the own workers in the organization and in the history of the Sindicato da Indústria Alimentícia de Concórdia Sintrial (Concórdia s Union of Food Industry). The text discusses, even though from a panoramic point of view, the classical national authors who write about the Unionism, not intending to re-study its history, but considering them as debate guides. Us dedicated to an analysis of the Sadia company, its appearance and establishment in the local, national and international market, so that we can show, even if only as a background, the changes that the company promotes in the local work market or, in its turn, the mutations which are imposed by the productive scenario to the organization, once the organization reflects the place where it s inserted